The empusium ebook A health resort horror story. - Tokarczuk, Olga (2024)
AN INSTANT NATIONAL BESTSELLER! A NEW YORK TIMES NOTABLE BOOK OF THE YEAR “A folk horror story with a deceptively light and knowing tone … elegant and genuinely unsettling.” – The New York Times Book Review The Nobel Prize winner’s latest masterwork, set in a sanitarium on the eve of World War I, probes the horrors that lie beneath our most hallowed ideas September 1913. A young Pole suffering from tuberculosis arrives at Wilhelm Opitz’s Guesthouse for Gentlemen in the village of Görbersdorf, a health resort in the Silesian mountains. Every evening the residents gather to imbibe the hallucinogenic local liqueur and debate the great issues of the day: Monarchy or democracy? Do devils exist? Are women born inferior? War or peace? Meanwhile, disturbing things are happening in the guesthouse and the surrounding hills. Someone—or something—seems to be watching, attempting to infiltrate this cloistered world. Little does the newcomer realize, as he tries to unravel both the truths within himself and the mystery of the sinister forces beyond, that they have already chosen their next target.   A century after the publication of The Magic Mountain , Olga Tokarczuk revisits Thomas Mann territory and lays claim to it, with signature boldness, inventiveness, humor, and bravura.